Clinical and economic burden of varicella in pediatric patients hospitalized in four institutions in Guatemala. - Mario Melgar; Ingrid Sajmolo; André Chocó; Lidia Ortiz; Ana Gabriela Cordova; Luis Hernández; Irwing Rivera; Ashly Zuñiga; Claudia Beltrán; Sebastian Medina; Marcel Marcano-Lozada (PLOS Global Public Health)
Varicella presents a public health challenge in Guatemala, with limited evidence regarding its impact; vaccine is currently absent from the national immunization program. Generating local data on the economic and health burden can support immunization policies. This study describes the use of hospital resources, costs of care, clinical and demographic characteristics, and complications in children with varicella. A retrospective review of medical records from patients admitted in four public institutions in Guatemala between January 2015 and December 2019, with diagnosis of varicella was performed. A total of 124 hospitalized patients, aged 0 to 14 years, were analyzed, of whom 46% had cancer. The average cost of hospitalization was USD 3,793.24 for complicated cases and USD 1,131.11 for uncomplicated cases. The average hospital stay was 11 days for patients with complications and 5 days for those without complications. In total, 66.1% of patients presented complications, with related infection complications being the most common. In conclusion, hospitalizations for varicella impose a significant economic and clinical burden in Guatemala. Complications increase the cost of care by three times, highlighting the importance of considering the inclusion of the varicella vaccine in the National Immunization Program to prevent the disease.